Trait Emotional Intelligence and Classroom Emotions: A Positive Psychology Investigation and Intervention Among Chinese EFL Learners - Li, Chengchen; Xu, Jinfen (Frontiers in Psychology, 2019)
The link between emotional intelligence (EI) and negative emotions, especially anxiety, has been investigated in different educational contexts including second/foreign language (L2) learning contexts. However, the link between EI and positive ones remains underexplored, despite second language acquisition (SLA) researchers’ growing interest in positive emotions motivated by the Positive Psychology (PP) movement. Grounded on PP theories, a correlational and experimental investigation was conducted on EI and two typical L2 classroom emotions, namely Foreign Language Enjoyment (FLE) and Anxiety (FLA). For the correlational study, questionnaires were administered among 1,718 English learners of three high schools in China. Statistical results showed medium correlations among students’ EI, FLE and FLA. In the intervention study, a pre-test, treatment and post-test design was adopted. A six-week PP-based EI intervention (“ARGUER” training model in class and the “three activities” of PP in diary) was conducted in the experiment class of 56 students, while not in the control class of 52 students. Semi-structured interviews were conducted with five students in the experimental class and their English teacher. ANCOVA test results and qualitative findings indicated that the EI intervention was effective in improving EI, boosting more positive classroom emotions and alleviating negative classroom emotions. The findings in both the correlational and intervention studies were discussed in combination with previous studies. We further addressed their theoretical and practical implications for L2 education.